Communities of practice for supporting health systems change: a missed opportunity. Issue 1 (December 2015) - Kothari, Anita; Boyko, Jennifer; Conklin, James; Stolee, Paul; Sibbald, Shannon
Abstract Background Communities of practice (CoPs) have been used in the health sector to support professional practice change. However, little is known about how CoPs might be used to influence a system that requires change at and across various levels (i.e. front line care, organizational, governmental). In this paper we examine the experience of a CoP in the Canadian province of Ontario as it engages in improving the care of seniors. Our aim is to shed light on using CoPs to facilitate systems change. Methods This paper draws on year one findings of a larger multiple case study that is aiming to increase understanding of knowledge translation processes mobilized through CoPs. In this paper we strategically report on one case to illustrate a critical example of a CoP trying to effect systems change. Primary data included semi-structured interviews with CoP members (n = 8), field notes from five planning meetings, and relevant background documents. Data analysis included deductive coding (i.e. pre-determined codes aligned with the larger project) and inductive coding which allowed codes and themes to emerge. A thorough description of the case was prepared using all the coded data. Results The CoP recognized a need to support health professionals (nurses, dentists) and related paraprofessionals with knowledge, experience, and resources to appropriately address their clients' oral health care needs. Accordingly, the CoP led a knowledge-to-action initiative that involved a seven-part webinar series meant to transfer step-by-step, skill-based knowledge through live and archived webinars. Although the core planning team functioned effectively to develop the webinars, the CoP was challenged by organizational and long-term care sector cultures, as well as governmental structures within the broader health context. Conclusion The provincial CoP functioned as an incubator that brought together best practices, research, experiences, a reflective learning cycle, and passionate champions. Nevertheless, the CoP's efforts to stimulate practice changes were met with broader resistance. Research about how to use CoPs to influence health systems change is needed given that CoPs are being tasked with this goal.